2017
DOI: 10.29080/jhsp.v1i1.16
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review againts Risk Factors on The Low-weight Birth Incidence in Indonesia

Abstract: The number of maternal and infant mortality in Indonesia is still high. Most of Indonesian neonatal mortality occurs in the first week of life with low-weight birth (LwB) / premature as the main cause. Birth weight is an important and reliable indicator for the survival of neonates and infants, both in terms of physical growth and development of the mental status. LwB caused by many complicated factors that related each others as if maternal factors that also affect the baby's weight at their birth. The purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
(5 reference statements)
1
5
0
Order By: Relevance
“…This study found that there is a significant relationship with neonatal birth weight (0.049). This founding is aligned with a systematical review conducted by Kusumawati [12] where two journals were found to have significant relationship with low birth weight with OR of 1,711 and 52,111, with a minimal of 4 visits. Antenatal care visits are very important for pregnant women as it helps them to take care of their physical and mental wellbeing, educating, detecting abnormalities, such that regular antenatal care visit will help quickly resolve any risks of causing abnormalities.…”
Section: Antenatal Care Visits Towards Neonatal Birth Weightsupporting
confidence: 81%
See 1 more Smart Citation
“…This study found that there is a significant relationship with neonatal birth weight (0.049). This founding is aligned with a systematical review conducted by Kusumawati [12] where two journals were found to have significant relationship with low birth weight with OR of 1,711 and 52,111, with a minimal of 4 visits. Antenatal care visits are very important for pregnant women as it helps them to take care of their physical and mental wellbeing, educating, detecting abnormalities, such that regular antenatal care visit will help quickly resolve any risks of causing abnormalities.…”
Section: Antenatal Care Visits Towards Neonatal Birth Weightsupporting
confidence: 81%
“…However, this is not aligned with study by Pertiwi et al [11], where no relationship was found between maternal age and low birth weight. Though maternal age acts as a risk of low birth weight, it is not the main factor of low birth weight, as there is a need to also consider other the factors [12,13). Analysis found that there is no correlation between maternal level of education and neonatal birth weight (p=0.265).…”
Section: Maternal Age Towards Neonatal Birth Weightmentioning
confidence: 99%
“…Birth weight is an important and reliable indicator that used as a general indicator to determine the health, nutrition and socio-economic status of developed and developing countries. Unbalanced birth weight can cause complications for both mother and baby [23]. This study showed that children who were born with LBW have an opportunity to be stunting 3,12 times larger than children who were born with normal weight after controlled by child sex, some family members, education level of the father and mother, mother's working status and average parents income.…”
Section: Discussionmentioning
confidence: 76%
“…Nutritional interventions such as dietary supplements during pregnancy in adolescents, women of childbearing age and during pregnancy helps reduce the occurrence of LBW [25]. Antenatal services aim to maintain the physical/mental health of mothers and infants by providing health education on nutrition and early detection of fetal abnormalities so if there are any abnormalities, it that can be quickly handled, especially the problem of fetal growth [23].…”
Section: Discussionmentioning
confidence: 99%
“…Babies who do not meet the normal estimation criteria are a vulnerable group that affects their health status (Farida, 2018). So, birth weight becomes an important indicator of infant health, both in terms of physical and cognitive development (Kusumawati, 2017). Babies with low birth weight status will be physically more susceptible to metabolic disorders in the future (Saragih & Yovsyah, 2017).…”
Section: Introductionmentioning
confidence: 99%